2009
DOI: 10.1111/j.1365-2141.2009.07886.x
|View full text |Cite
|
Sign up to set email alerts
|

The allogeneic graft‐versus‐cancer effect

Abstract: SummaryAllogeneic haematological stem cell transplantation (HSCT) has developed into immunotherapy. Donor CD4 + , CD8 + and natural killer (NK) cells have been reported to mediate graftversus-leukaemia (GVL) effects, using Fas-dependent killing and perforin degranulation to eradicate malignant cells. Cytokines, such as interleukin-2, interferon-c and tumour necrosis factor-a potentiate the GVL effect. Post-transplant adoptive therapy of cytotoxic T-cells (CTL) against leukaemiaspecific antigens, minor histocom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
90
0
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(97 citation statements)
references
References 239 publications
(270 reference statements)
2
90
0
5
Order By: Relevance
“…[30][31][32][33][34] However, it has also been observed in patients with solid tumours. [35][36][37] Similar to haematologic malignancies, the disease status at the time of HSCT and the occurrence of chronic GvHD are strong predictive outcome parameters. Patients with t-MNs and a primary malignancy not in CR are, however, ineligible for allo HSCT in many centres, donor registries and clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…[30][31][32][33][34] However, it has also been observed in patients with solid tumours. [35][36][37] Similar to haematologic malignancies, the disease status at the time of HSCT and the occurrence of chronic GvHD are strong predictive outcome parameters. Patients with t-MNs and a primary malignancy not in CR are, however, ineligible for allo HSCT in many centres, donor registries and clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…The GVL effect is mediated by donor-derived allogeneic T cells directly attacking the leukemic cells [2]. This advantageous effect was elegantly described by Horowitz et al [21] who observed that patients who received identical twin transplants had an increased probability of relapse compared with allograft recipients.…”
Section: Graft Versus Leukaemia As An Immunological Tool After Sctmentioning
confidence: 74%
“…o r g most common long-term complication and occurs in 30% to 70% of adults who survive for more than 100 days after receiving their transplantation [3]. cGVHD has been associated with a reduced risk of relapse, possibly because of a concomitant graft-versus-leukemia effect [4][5][6]. Despite this, cGVHD correlates with increased morbidity and mortality and has a major impact on the quality of life of subjects who have undergone allo-HSCT [7].…”
Section: Introductionmentioning
confidence: 99%